Views on the Imperative of EU-US Relations - Avar, Yusuf; Lin, Yu Chou (Budapest International Research and Critics University, 2021)
The EU Member States share various perceptions and preferences on lots of Union’s issues, particularly in the areas of foreign and security policies. Some countries, such as France, Belgium, and Luxembourg, focus on the establishment of the European autonomous defence. Others, especially most of the Central and Eastern European countries, as well as the UK, supported the transatlantic burden sharing. The neutral states also concur with the concept of transatlantic burden sharing. However, the transatlantic relations between the EU and the US are problematic. This study argues that the EU would increase its importance to the role of international politics to effectively implement its goals if the transatlantic relations are stable. The EU requires the military capability and leadership of the US; on the other hand, the US also relies on the EU’s peacemaking and peacekeeping capacity. When both blocs closely cooperate with each other as an important partnership to counter international terrorism, regional disputes, climate change, failed states, mass movements of migration, epidemic diseases, and so on, they would respond to these problems and resolve them within a shorter time.